Inhibition of melanoma using a nanoceria-based prolonged oxygen-generating phototherapy hydrogel - Zhang, Lidong; Liu, Xiaoguang; Mao, Yinghua; Rong, Shu; Chen, Yonghong; Qi, Yong; Cai, Zhipeng; Li, Hong (Frontiers in Oncology, 2023)
Tumor hypoxic environment is an inevitable obstacle for photodynamic therapy (PDT) of melanoma. Herein, a multifunctional oxygen-generating hydrogel loaded with hyaluronic acid-chlorin e6 modified nanoceria and calcium peroxide (Gel-HCeC-CaO2) was developed for the phototherapy of melanoma. The thermo-sensitive hydrogel could act as a sustained drug delivery system to accumulate photosensitizers (chlorin e6, Ce6) around the tumor, followed by cellular uptake mediated by nanocarrier and hyaluronic acid (HA) targeting. The moderate sustained oxygen generation in the hydrogel was produced by the reaction of calcium peroxide (CaO2) with infiltrated H2O in the presence of catalase mimetic nanoceria. The developed Gel-HCeC-CaO2 could efficiently alleviate the hypoxia microenvironment of tumors as indicated by the expression of hypoxia-inducible factor -1α (HIF-1α), meeting the “once injection, repeat irradiation” strategy and enhanced PDT efficacy. The prolonged oxygen-generating phototherapy hydrogel system provided a new strategy for tumor hypoxia alleviation and PDT.